2012
DOI: 10.1002/jmv.23212
|View full text |Cite
|
Sign up to set email alerts
|

Development of a hepatitis delta virus antibody assay for study of the prevalence of HDV among individuals infected with hepatitis B virus in China

Abstract: Co-infection with hepatitis delta virus (HDV) and hepatitis B virus (HBV) has been shown to be associated with a more severe form of acute and chronic hepatitis. Cloning and expression of recombinant HDV antigen (rHDAg) in Escherichiacoli are described. Using purified rHDAg, a cost-effective indirect anti-HDV enzyme-linked immunosorbent assay (ELISA) kit was developed. Direct comparison of 15 known HDV-positive sera and 15 HDV-negative sera showed concordance agreement between the new assay kit and the Abbott … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The hepatitis B surface antigen (HBsAg) prevalence in the total population in a national survey was estimated to be 9.75% in 1992 and 7.18% in 2006 [25] . Similarly, HDV prevalence in HBV infected individuals was found to be 0.8–12% (mean 6.4%) in different provinces of China in the 1990's [40] . Shen et al suggested a lower prevalence of HDV in HBV infected individuals in China (lower in comparison to <6% prevalence in other parts of the world) [40] .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The hepatitis B surface antigen (HBsAg) prevalence in the total population in a national survey was estimated to be 9.75% in 1992 and 7.18% in 2006 [25] . Similarly, HDV prevalence in HBV infected individuals was found to be 0.8–12% (mean 6.4%) in different provinces of China in the 1990's [40] . Shen et al suggested a lower prevalence of HDV in HBV infected individuals in China (lower in comparison to <6% prevalence in other parts of the world) [40] .…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, HDV prevalence in HBV infected individuals was found to be 0.8–12% (mean 6.4%) in different provinces of China in the 1990's [40] . Shen et al suggested a lower prevalence of HDV in HBV infected individuals in China (lower in comparison to <6% prevalence in other parts of the world) [40] . Since HDV prevalence in HBV infected individuals in China in 1992 is unknown, we used this observation and assumed HDV prevalence to be 3.2% at the commencement of HBV vaccination in 1992 (range of 0% to 6.4% HDV prevalence [40] ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…First, control subjects in the study were only tested for HBsAg, but not for other serum markers of HBV. Second, case subjects were not tested for coinfection with hepatitis D virus (HDV), athough the prevalence of HDV and HBV coinfection is relatively low in China . In addition, no history of HDV infection was self‐reported.…”
Section: Discussionmentioning
confidence: 99%
“…The assays described in those studies have been discontinued or are no longer available in the United States. More recently developed HDV immunoassays have been mainly limited to research purposes or clinical use in local institutions (8)(9)(10). In this study, we evaluated two commercially available enzyme immunoassays (EIAs) for detecting anti-HDV antibodies and compared the data with those obtained in two reference laboratories.…”
mentioning
confidence: 99%